Efeito do tabagismo no perfil de metilação e hidroximetilação global de DNA e nos genes MIR-9-3 e MIR- 137 em mucosa oral - Costa, Ludimila de Araújo (2016)
Epigenetic is the study of inherited and reversible changes in functional genome that do not alter the sequence of nucleotide bases. Modulate gene expression mainly by interference of external factors, such as smoking. MicroRNAs are a family of small post transcriptional regulatory RNAs genes which expression can also be controlled by DNA methylation.The aim of this study was to investigate the influence of smoking on the methylation and hydroxymethylation status of global DNA and specific sites of miR-9-3 and miR-137 genes in the healthy oral mucosa. Samples of oral epithelial cells were collected using mouthwash from a population of 95 individuals who were divided into three groups according to smoking status: never (n=30), current (n=29) and former smokers (n=36). Genomic DNA was extracted, and global DNA methylation and hydroxymethylation was performed using an ELISA-based technique; DNA methylation at specific sites of miR-9-3 and miR-137 was performed using methylation-specific PCR. Higher levels of global DNA methylation were found in current smokers with over 15 years of consumption, but no differences were found in relation to global DNA hydroxymethylation. Global DNA methylation was higher than the hydroxymethylation level but they were not correlated in the oral mucosa. For specific sites, the miR-137 promoter had partially methylated DNA in all groups and miR-9-3 hypomethylation was detected in current smokers in comparison to never and former smokers. There were no differences in epigenetic marks analyzed in relation to gender and age. We concluded that smoking habits were capable of inducing changes in global DNA methylation and miR-9-3 promoter methylation status.